2011
DOI: 10.1373/clinchem.2010.152025
|View full text |Cite
|
Sign up to set email alerts
|

Computational Methods Are Significant Determinants of the Associations and Definitions of Insulin Resistance Using the Homeostasis Model Assessment in Women of Reproductive Age

Abstract: BACKGROUND:Insulin resistance (IR) plays an important role in the pathogenesis of polycystic ovary syndrome (PCOS), but identification of insulin-resistant individuals is difficult. The homeostasis model assessment (HOMA), a surrogate marker of IR, is available in 2 computational models: HOMA1-IR (formula) and HOMA2-IR (computer program), which differ in incorporated physiological assumptions. This study evaluates the associations of the 2 models as markers of IR, the metabolic syndrome (MS), and PCOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…In another study, HOMA2 more significantly affected the identification of IR and the detection of metabolic syndrome and polycystic ovarian disease than HOMA1 [18]. In this study, HOMA1-IR and HOMA2-IR were not significantly different in their ability to predict the progression to T2DM in the NGT group, but HOMA2, especially HOMA2-β, was more predictive in pre-diabetic and non-diabetic Koreans than HOMA1.…”
Section: Discussionmentioning
confidence: 49%
“…In another study, HOMA2 more significantly affected the identification of IR and the detection of metabolic syndrome and polycystic ovarian disease than HOMA1 [18]. In this study, HOMA1-IR and HOMA2-IR were not significantly different in their ability to predict the progression to T2DM in the NGT group, but HOMA2, especially HOMA2-β, was more predictive in pre-diabetic and non-diabetic Koreans than HOMA1.…”
Section: Discussionmentioning
confidence: 49%
“…HOMA-IR score was calculated during the adaptation period, weeks 6, 11, and 12, with a HOMA-IR calculator. 37 Numbers represent means ± SE ( n = 5–8). Means with different letters are significantly different at P < 0.05.…”
Section: Resultsmentioning
confidence: 99%
“…If the same cut-off has been selected as criterion in this study, more than 10% of healthy lean controls with WC<80 cm would be identified as being IR. Therefore, the use of pre-selected HOMA-IR cut-off for identifying those with IR should be discouraged since, even in the ethnically homogeneous population, substantial differences in HOMA-IR cut-off value used could have an influence on identification of insulin resistant women and therefore, their healthcare management [9,31].…”
Section: Resultsmentioning
confidence: 99%